Wicked cool Java : code bits, open-source libraries, and project ideas - Eubanks, Brian D. (No Starch Press, 2005)
Wicked Cool Java contains 101 fun, interesting, and useful ways to get more out of Java. Full of example code and ideas for combining the code examples into useful projects, this book is perfect for hobbyists and professionals looking for tips and open source projects to enhance their code and make their jobs easier. Topics include converting a non-XML text structure into XML using a parser generator, experimenting with a Java simulator for the Cell Matrix, creating dynamic music and sound in Java, working with open source class libraries for scientific and mathematical applications, and many.